Anti-MRSA Activity of Few Indian Medicinal Plants - Salkar, Kavita; Suthar, Ashish; Chauhan, VijaySingh; Naik, Vinayak (Asian Journal of Biological and Life Sciences, 2013)
The report of emergence of resistant strains of S.aureus like MRSA is increasing day by day. With a view to get new antimicrobial, plants belonging to different families alleged to possess antimicrobial properties were studied against the antibiotic-resistant strains of bacteria. The eighteen plants were selected for anti bacterial activity based on the literature search from different regions of India. The various plant parts were collected, dried and than extracted using three different solvents viz. methanol, hydro-methanol and aqueous. The extracts so prepared were tested against the bacterial strains which are standard ATCC cultures procured and maintained in the lab. For anti bacterial screening, we used strains of Gram positive bacteria -S.aureus 209P and Methicillin Resistant S.aureus (MRSA) strains. Out of the eighteen plants studied seven were found to be active with zone of inhibition against all the tested bacterial species. New sources of anti infectious agents should be studied with a view to get potent antimicrobials which can tackle resistance problem.